EVOLUTION AND PERSPECTIVES OF TIMED ARTIFICIAL INSEMINATION (TAI) PROGRAMS IN BRAZIL - A REVIEW - CARVALHO, NAT; SOARES, JG; BARUSELLI, PS (The Indian Journal of Animal Reproduction, 2022)
Timed artificial insemination (TAI) has been applied worldwide to improve the reproductive efficiency and enhance genetic gain of buffalo herds. The control of emergence of follicular waves and of ovulation at predetermined times, without the need for estrus detection, has facilitated the management and improved the efficiency of AI programs in buffalo during the breeding and nonbreeding season in Brazil. Currently, timed ovulation induction and TAI can be performed in buffalo using GnRH or estradiol plus progesterone/progestin (P4)-releasing devices and prostaglandin F2α (PGF2α). The use of TAI protocols contributed to dissemination of AI in buffalo herds, which allowed genetic improvement and, consequently, an increase in milk and beef production of this species.